AB0579 ANTI-JO1 ANTIBODIES IN A REAL-WORLD POPULATION. (2nd June 2020) - Greco, M.; García de Yébenes, M. J.; Nóvoa Medina, F. J.; Hernandez Beriain, J. A.; Riaño Ruiz, M. M.; Montesa, M. J.; Rua-Figueroa, I.; Loza, E.; Carmona, L.
Abstract : Background: The presence of anti-aminoacyl transfer RNA synthetase (ARS) autoantibodies is essential for the antisynthetase syndromes (ASSD) diagnosis; as well, Anti-Jo1 ARS positivity is the highest weighted criterion in the 2017 EULAR/ACR criteria for idiopathic inflammatory myopathies (IIM). Previous studies have shown differences in ARS specificity between different blot assays. Nevertheless, an adequate clinical correlation and its detection by another monospecific-assays or indirect immunofluorescence assay (IIFA), can safeguard it. Objectives: To evaluate the prevalence of Anti-Jo1 ARS and their performance in the ASSD and IIM diagnosis criteria fulfillment in a real-world population. Methods: We performed an observational retrospective study in one center in which IIFA and a blot assay (EUROLINE ANA Profile 3-IgG that include Anti-Jo1 but not other ARS) were performed in all cases with autoimmune disease suspicion (03/2007-07/2019). We assessed: 1) Anti-Jo1 ARS prevalence, 2) The rate of Anti-Jo1 positivity in the performed blot assays, 3) The rate of patients with Anti-Jo1 ARS meeting ASSD or IIM criteria, and 4) The rate of true and false positive Anti-Jo1 ARS considering the IIFA and clinical correlation. Results: A total of 419.361 inhabitants are under the center coverage area at the date, a total of 12.711 blot assays were performed during the observation period, and 61 cases presented Anti-Jo1 ARS positivity. The Anti-Jo1 ARS prevalence in the whole studied population was 0.00014, representing 0.04% positivity of the performed blot assays. Of those with Anti-Jo1 positivity: – Only 4 patients (6.6%) met Solomon´s ASSD criteria and 26 (42.6%) met Connors ASSD criteria (less strict), representing the 0.0009% and 0.006% of the whole population respectively. – Five cases (8.2%) presented a possible or probable IIM by Bohan and Peter criteria and 55 cases (90.16%) presented a probable or definitive IIM by EULAR/ACR criteria, representing 0.001% and the 0.013% of the whole population respectively. – The Anti-Jo1 positivity was not confirmed by a monospecific-assay. Nevertheless, 52 cases (85.25%) presented positive IIFA (>1/80): 27 (51.92%) nuclear, 12 (23.08%) cytoplasmic and 12 (25%) with both patterns. A total of 23 cases presented a fine speckled AC-19/AC-20 pattern; representing the 40.98% of all Anti-Jo1 ARS cases. – Only 4 cases (6.56%) did not meet any of the ASSD or IIM classification criteria. And only 4 cases (6.56%) fulfilled Solomon ASSD criteria or presented a probable IIM by Bohan and Peter criteria, or a definite IIM by EULAR/ACR criteria. Thus, we can estimate that 6.56% of the cases were clinically false positives and other 6.56% were clinically true positive; leading a gap of 86.88% of cases with Anti-Jo1 ARS that only fulfill Connors ASSD criteria (less strict) or a not complete score to confirm the IIM diagnosis by Bohan and Peter or EULAR/ACR criteria. Conclusion: The low prevalence of Anti-Jo1 ARS positivity observed and the low number of cases with confirmed ASSD or IIM in the Anti-Jo1 positive detected cases, suggest that: – It is not efficient to test it by screening. – It should be tested only under adequate clinical suspicion. – Probably it is not convenient to include it in not myositis specific blot assays. Despite it is desirable to incorporate the evaluation of myositis specific antibodies in the IIM classification criteria; the differences observed between Bohan and Peter and 2017 EULAR/ACR criteria fulfillment in our series, suggest that the latter could be overweighting the Anti-Jo1 ARS positivity. Disclosure of Interests: Martín Greco: None declared, María Jesús García de Yébenes: None declared, Francisco Javier Nóvoa Medina Speakers bureau: I have been paid as a speaker for a few medical talks, José A Hernandez Beriain: None declared, Marta María Riaño Ruiz: None declared, María Jesús Montesa: None declared, Iñigo Rua-Figueroa: None declared, Estíbaliz Loza Grant/research support from: Roche, Pfizer, Abbvie, MSD, Novartis, Gebro, Adacap, Astellas, BMS, Lylly, Sanofi, Eisai, Leo, Sobi, Loreto Carmona Grant/research support from: Novartis Farmaceutica, SA, Pfizer, S.L.U., Merck Sharp & Dohme España, S.A., Roche Farma, S.A, Sanofi Aventis, AbbVie Spain, S.L.U., and Laboratorios Gebro Pharma, SA (All trhough institution)